Réflexions de nature conceptuelle sur la sociologie du droit de Max Weber au regard de sa Wissenschaftslehre - Treiber, Hubert (SocietàMutamentoPolitica, 2023)
That Weber’s essay on Stammler provides insights and concepts for the sociology of law is self-evident. In the following we will examine whether this is also true of his epistemology as a whole. First, we will present Stammler’s basic assumptions, which are in part contradictory (because they confuse being and ought to be), on the basis of Sinzheimer, following Coutu (2013). We refer to Sinzheimer because he presents the main criticisms of Stammler in a clear and pertinent way, which is confirmed by a reading of Stammler’s Wirtschaft und Recht. We then make a brief detour via Heinrich Popitz’s 1980 study Die normative Konstruktion von Gesellschaft. Finally, we extend the significance of Stammler’s critique of Weber’s sociology of law, highlighted by Coutu (2013), to other components of his theory of science.